Self-diffusion in granular gases - Brilliantov, Nikolai; Pöschel, Thorsten (Physical Review E, 2000)
The coefficient of self-diffusion for a homogeneously cooling granular gas changes significantly if the impact-velocity dependence of the restitution coefficient ε is taken into account. For the case of a constant ε the particles spread logarithmically slowly with time, whereas a velocity-dependent coefficient yields a power law time dependence. The impact of the difference in these time dependences on the properties of a freely cooling granular gas is discussed.